Stretching our safety net almost to breaking point - Martín López, Berta (2020)
Nature is essential for human existence and a goodquality of life, providing and sustaining the air, freshwater and soils on which humanity depends. Italso regulates the climate, provides pollination and pest control, and reduces the impact of natural hazards.While more food, energy and materials than ever before are being supplied to people in most parts ofthe world, this is increasingly coming at the expense of nature’s ability to provide them in the future, withthe over exploitation of plants and animals frequently undermining nature’s many other contributions 13, 99.Within the Intergovernmental Science-Policy Platformon Biodiversity and Ecosystem Services (IPBES)conceptual framework, these contributions are referred to as ‘Nature’s Contributions to People’ 13, 99. This table was included in the IPBES Summary for Policy makersand it presents the global trends for some of these contributions from 1970 to the present day: we explore these concepts in more detail in the final section ofthis chapter.